Synthesis of polyacrylonitrile nanoflowers and their controlled pH-sensitive drug release behavior. Issue 27 (21st April 2020) - Lian, Qi; Liu, Han; Zheng, Xuefang; Jia, Dandan; Liu, Chun; Wang, Dongjun
Abstract : The schematic preparation of a new kind of pH-sensitive PAN nanoflower and its potential application for UC therapy. PAN (TBP) nanoflowers at pH 7.4 showed good sustained-release ( t 83% = 260 h), which best fitted the Riger–Peppas model. Abstract : A novel controlled drug release system based on pH sensitive polyacrylonitrile (PAN) nanoflowers in different kinds of solvents was successfully prepared with azobisisobutyronitrile (AIBN) as the initiator and without any emulsifier or stabilizer by a one step static polymerization method. The composition and structure of the PAN nanoflowers were analyzed by FTIR, XRD, SEM, TEM, and laser particle size analysis. The polymer particles consisted of a number of lamellae, with a sheet thickness of about 10 nm, and were similar to the shape of flowers with a particle diameter of about 350 nm. The mechanism of the polymerization reaction and the formation were studied. Moreover, the effects of monomer ratio, initiator concentration, reaction time, dispersion medium and co-monomer on the morphology and particle size of the nanoflowers were also discussed. A relatively large specific surface area was formed during the formation of the nanoflowers, which favored drug adsorption. The results of the in vitro experiments revealed that PAN(TBP) nanoflowers, containing BSA in buffer solution of pH 7.4, demonstrated good sustained-release and the cumulative release rate was about 83% after 260 h. The results also showed that the sustained-release from the PAN(TBP) nanoflowers best fitted the Riger-Peppas model. This study indicated that PAN(TBP) nanoflowers provided a theoretical base for the development of carriers for sustainable drug-release.